Effect of high temperature aging on the performance of nanoCu sintered joints - Lim, Rachel Ai Ying (Nanyang Technological University, 2021)
Harsh environment electronics need to maintain their functionality while working at conditions such as under high current density, high operating frequency and high working temperature for power electronics devices. To realise the favourable performance of such devices, the package and assembly technology of the dies are also critical. For the die attach material which helps to bond the die and substrate together, it will greatly influence the operating performance and reliability of these power devices in the long run. As current die attach materials will typically degrade at around 250°C and cannot maintain high temperature stability, novel joining materials are needed to satisfy the requirements. Among which, Cu nanoparticles (NanoCu) sintering material is a potential candidate for power electronics due to its low bonding temperature, high operation temperature, remarkable electrical and thermal conductivity, while having lower cost compared to Ag nanoparticles (NanoAg) sintering material. However, NanoCu particles are very susceptible to oxidation during sintering. Also, the performance of NanoCu sintered joint during prolong high temperature aging is questionable due to limited research studies done. This study aims to bridge the reliability gaps by characterising the evolution of porosities and microstructures of the sintered NanoCu joints, sandwiched between a Cu die and substrate, after thermal storage in air at 300°C for various times. The average die shear strength of the sintered NanoCu joint was observed to peak at 17 MPa after 200 h and maintained at 14 MPa after 600 h of thermal storage test. The initial increase in the average die shear strength can be attributed to the densification of the sintered NanoCu joints with regards to a decrease in the total volume of porosity. These results suggest that the use of pressure-less NanoCu joint sintering could emerge as a new die attach material for high temperature devices.